Performance evaluation of different cationic flocculants through pH modulation for efficient harvesting of Chlorella sp. HS2 and their impact on water reusability. (June 2019) - Nayak, Manoranjan; Rashid, Naim; Suh, William I.; Lee, Bongsoo; Chang, Yong Keun
Abstract: Flocculation is an effective technique for harvesting microalgae due to low energy input and being scalable up to industrial algaculture. In this study, four different flocculants at various concentration, and pH levels were employed for the harvesting of Chlorella sp. HS2. Among the tested flocculants, chitosan showed the highest flocculation efficiency of 99.6% ± 0.25 at 10 mg L −1 dosage, pH 8.0 and 30 min of sedimentation. It turned out that the choice of flocculants had minimum impact on the fatty acids methyl ester (FAME) yield and composition. When the reusability of the spent medium for each flocculant was investigated, the culture supernatant obtained from chitosan-based harvesting method had lower growth inhibitory effects in comparison to those harvested using the other flocculants. The cost analysis also favored chitosan-based flocculation, because it returned the highest flocculant efficiency while the flocculant dosage was the lowest. Due to its high harvest efficiency and low impact on the water footprint, it was concluded that the chitosan offer promising advantages over other flocculants. Graphical abstract: Image 103955 Highlights: Flocculation of Chlorella sp. HS2 with various cationic flocculants was evaluated. Flocculation efficiency can enhanced by modulation of medium pH. Highest flocculation efficiency of 99.6% was achieved using chitosan at pH 8. Reusability of the medium is dependent on the type of flocculant that is used.